EMPATHY AND PSYCHOLOGICAL WELL-BEING: A REVIEW - Manav Mohan Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Empathy and psychological well-being (PWB) are often talked about as two sides of the same coin in positive psychology--and for good reason. They both play vital roles in how people connect with others, manage stress, and maintain emotional balance. This review looks at ten studies exploring how empathy relates to well-being across different groups, including teenagers, married couples, healthcare workers, designers, peer support staff, and postgraduate students. While most research shows that empathy and well-being go hand in hand, the strength of this relationship varies depending on age, gender, and professional context. Some studies dive deep into the emotional side of empathy, others highlight its social power, but all face common challenges: small samples, cross-sectional designs, and heavy reliance on self-report tools. Still, the takeaway is clear--empathy matters. It's a meaningful, though sometimes complex, contributor to our mental health. Understanding how to nurture it could open new doors in education, therapy, and workplace wellness.